Microalbuminuria and Traditional Serum Biomarkers of Nephropathy among Diabetic Patients at Mbarara Regional Referral Hospital in South Western Uganda - Ritah Kiconco; Simon Peter Rugera; Gertrude N. Kiwanuka (Journal of Diabetes Research)
Background. Diabetic nephropathy (DN) is a common finding in diabetic patients. Microalbuminuria is the earliest clinical evidence of DN. Early detection of microalbuminuria is very important; it allows timely interventions to prevent progression to macroalbuminuria and later end-stage renal disease (ESRD). Objectives. To determine the prevalence of microalbuminuria in diabetic patients and establish its association with traditional serum renal markers in assessment of incipient nephropathy. Methods. This cross-sectional study involved 140 participants with diabetes mellitus (DM) attending the diabetic clinic of Mbarara Regional Referral Hospital. Questionnaires were used to obtain participant data after obtaining written informed consent. Data collected included: age, sex, level of education, history of smoking and alcohol consumption, hypertension, body mass index, family history, and duration of DM. Morning spot urine samples were collected from each participant and blood drawn for analysis of other renal markers. Urine microalbumin was determined quantitatively using immunoturbidity assay (Microalbumin kit, Mindray). Serum creatinine and uric acid and glucose levels were determined by spectrophotometric methods. Results. The overall prevalence of microalbuminuria was 22.9%. Using a simple and multiple linear regression model, serum creatinine (β=0.010, 95% CI (0.005, 0.014), P=0.0001) and glucose (β=0.030, 95% CI (0.011, 0.048), P=0.0017) levels were significantly associated with microalbuminuria. After adjusting for linearity, family history of DM was the only predictor of microalbuminuria (β=0.275, 95% CI (0.043, 0.508), P=0.002). Although microalbuminuria was weakly associated with eGFR (OR=1.2, 95% CI (0.24, 5.96)), the relationship was not statistically significant (P=0.824). Conclusion. The prevalence of microalbuminuria in patients with diabetes in this study was high. The study suggests the need to screen for microalbuminuria early to reduce the possible burden of ESRD. When serum creatinine is used as a renal function marker among diabetic patients, it should be combined with microalbuminuria for better assessment of incipient nephropathy.